Tomographic imaging for reconstructing ionospheric distributions - Francisco Rubén Soria; Víctor Hugo Ríos (Geofísica Internacional, 1999)
The ionospheric system is analysed and modelled using tomographic imaging, formulated in three segments: the ionospheric data acquisition system, the model, and the reconstruction algorithm. The resolution limit of the system is analysed, followed by a quantitative measure of the complete imaging system’s resolving capability.